How to implement the IIUM Islamisation policy?:Some examples and models - Md. Noon, Hazizan (2015)
The lecture was meant to deliberate and discuss the ways to implement the IIUM Policies and Guidelines on Islamisation in International Islamic University Malaysia particularly at the Centre for Foundation Studies.